On the brink of social resistance: local community perceptions of mining company operating permits in East Luwu, Indonesia - Muhammad, Sawedi; Arifin, Suryanto; Syam, Ridwan; Putra, Bama Andika (Frontiers in Sociology, 2024)
The presence of a mining company in an area affects the living conditions of the surrounding community from an environmental, social, and economic perspective. This research aims to contribute to the literature on social perceptions concerning mining company operations by assessing the local societies’ rate of rejection or acceptance of a mining company’s extension of operating permit, along with reasons that justify the decision. We conducted semi-structured interviews with seven interest groups in four sub-districts in East Luwu Regency, comprising 79 participants. This research uses a combination of quantitative data collection and in-depth qualitative interviews to strengthen the sources’ reasons for providing answers. The results show a high rejection rate expressed by communities living in the sub-districts where mining companies operate, alongside a strong preference for extending operating permits for sites that are of greater distance to the smelters. If the business permit is ultimately transferred to the existing company, it may exacerbate community tensions and resistance. In that case, the local community wants several priority improvements, namely, increasing the number of workers working in the factory, further boosting economic growth and empowerment programs carried out in affected areas, and improving post-mining environmental management. Therefore, this study contributes to the discourse of local community perceptions in mining areas, which may affect mining operations in the future.